2005
DOI: 10.1520/gtj12130
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evaluation of the Hydraulic Conductivity of Compacted Lateritic Soil

Abstract: This paper examines the variation of hydraulic conductivity of a compacted lateritic soil with molding water content, dry unit weight, and initial degree of saturation under as-compacted conditions. Trends in the hydraulic conductivity versus molding water content relationships are similar to those obtained for nonlateritic, temperate zone soils. Hydraulic conductivity generally decreased as dry unit weight and initial degree of saturation increased. However, for the same values of dry unit weight, specimens c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results of the hydraulic conductivity tests conducted in the laboratory on compacted specimens were utilized in determining the compaction criterion for each soil and the compaction criterion then served as a guide for the construction of covers and soil liners in the field (Nwaiwu et al, 2005). Daniel (1993) showed that bentonite clay materials were the preferred hydraulic barriers due to their good adsorption/retention capacity and low hydraulic conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the hydraulic conductivity tests conducted in the laboratory on compacted specimens were utilized in determining the compaction criterion for each soil and the compaction criterion then served as a guide for the construction of covers and soil liners in the field (Nwaiwu et al, 2005). Daniel (1993) showed that bentonite clay materials were the preferred hydraulic barriers due to their good adsorption/retention capacity and low hydraulic conductivity.…”
Section: Introductionmentioning
confidence: 99%